Potensi dan Karakteristik Tingkah Laku Murid - Sukatin; Andri Astuti; Dinda Wulandari; Erika Gita Fahira; Fadhilah Angraeni; Alvi Darusadina Sapitri (Medan Resource Center, 2022)
Potential comes from the Latin, namely potentia which means ability, potential can be interpreted as a hidden basic ability and the results can be felt after the ability is developed. Potential is a very large resource that is not known and that has not been given at the time humans were born in this world. Potential is an ability that has not been opened, stored power, strength that has not been touched, success that has not been used, a hidden gift or in other words, potential is an ability or strength or power, where potential can be innate or talent and the result of stimulus or training in development. Potential is the ability, strength, ability, power that has the possibility to be developed. Basically, every student has potential, both physically, intellectually, personality, interests, morally, and religiously. should be honed from an early age so that the potential of children can develop optimally. And an effective way to develop children's potential is to apply effective and efficient learning models so that students can hone their abilities/potentials.